Emotions, traits, and intellect: a triadic exploration of adjustment and academic success in high school students - Rachna; Srivastava, Rani; Gairola, Parul (International Journal of Research in Medical Sciences, 2025)
Background: Adolescence is a crucial developmental stage where personality traits, intelligence quotient (IQ) and emotional intelligence (EI) significantly influence academic achievement and psychological well-being. Despite widespread belief in IQ as a predictor of success, recent research emphasises the growing relevance of EI and personality in fostering social and academic competence. Methods: A cross-sectional, correlational study was conducted across six secondary schools in Faridabad, India. A stratified random sample of 387 adolescents (aged 16–18 years) participated. Standardised tools were used: Raven’s Standard Progressive Matrices (RSPM) for IQ, Eysenck’s Personality Questionnaire (EPQ) and the Emotional Intelligence Scale (EIS). Statistical analyses included Pearson correlation, regression analysis and ANOVA. Results: The results indicated that IQ had a negligible effect on emotional intelligence (EI). Nevertheless, some personality traits, especially psychoticism and neuroticism, significantly affected emotional regulation and social adaptability. There were differences between men and women in emotional intelligence. Women were better at empathy and social skills, while men were better at self-regulation. Regression models demonstrated that psychoticism influenced the relationship between IQ and emotional intelligence (EI). Conclusions: This study shows that IQ isn't a great predictor of emotional intelligence and that personality factors are more important in molding social and emotional competence in teenagers. In order to improve academic resilience, self-esteem and stress control, the results support the implementation of interventions focused on emotional intelligence in educational settings. For teens to thrive academically, there must be an interdisciplinary approach to learning that prioritizes their emotional and cognitive development.